(3GdPgH GdEHQjR aj JaSjQ cJGH Gddg GdYRjRs - (3eMeO GdjOGdj Hf GdeNJGQ Hf eMeO SYjO GdOjeGfj,J (B1164 (3g` s
(3ChdgG (B:s
(3gOi hJHUQI hPcQi dChdi GdCdHGH hLYdg ai GdWHbI GdYdjG ef GdaUMGI hGdHjGf , MJi hLYdJg bQBfkG YQHjkG ZjQ Pi YhL hHYO ajbhd GdYHO eMeO Hf SYjO SejJg HGdOQ GdaQjO ai JaSjQ GdbQBf GdeLjO , hHGdPgH GdEHQjR s
(3BNQgG (B:s
( (3ef ShQI GdHbQI (B) (3hGJbhG jhekG JQLYhf HGdHfGA ddeaYhd bGd GdSjhWi (B: (3hdGefGaGI Hjf gPg GdQhGjGJ ai BjI GdQHG dCf GdXGgQ CfgeG fRdJG s
(3cJHJ HYV YHGQGJgG HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs